Small business in Japan 1985 : (Small and Medium Enterprise Agency, 1985)
Contents: Part 1. Recent trends in small and medium enterprises; Part 2. Tasks for small and medium enterprises in the age of innovation; Conclusion; Focuses in the fy 1985 measures for small and medium enterprises.